HUBUNGAN STATUS PEKERJAAN IBU DENGAN PEMBERIAN ASI PADA BAYI DI RW 006 KELURAHAN KRUKUT KECAMATAN LIMO KOTA SEHAT DEPOK - Rokhaidah Rokhaidah (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
Baby is a newborn individual creatures until up-to the age of 12 months-old. As a newborns, babies should be given breastfeeding by the mother because the babies whose fed on breastfeeding will healthier compared with babies that fed by formula milk. Exclusive breastfeeding is giving since the mother gived birth until the babies is 6 months-old and not getting additional food or others liquids such as formula milk, oranges and mineral water. The research aimed to find out the relationship between occupational status mothers with exclusive breastfeeding on babies. This research is a descriptive analytical study by using the Chi Square analysis on 49 respondents obtained with the method of purposive sampling. The results of this research showed there is no relationship between occupational status mothers with exclusive breastfeeding on babies (OR= 2,456 P Value 0,211 with alpha > 0,05). It is recommended for each family member, especially the husband to give a support and motivation to mother in giving exclusive breastfeeding to the babies.